2016
DOI: 10.1017/s0007114516000416
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of selenium tissue distribution and selenoprotein expression in Atlantic salmon (Salmo salarL.) fed diets with graded levels of plant ingredients

Abstract: Increased substitution of marine ingredients by terrestrial plant products in aquafeeds has been proven to be suitable for Atlantic salmon farming. However, a reduction in n-3 long-chain PUFA is a consequence of this substitution. In contrast, relatively little attention has been paid to the effects of fishmeal and oil substitution on levels of micronutrients such as Se, considering fish are major sources of this mineral for human consumers. To evaluate the effects of dietary marine ingredient substitution on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
(80 reference statements)
2
17
0
Order By: Relevance
“…Despite increased total fish consumption in Bangladesh in the past two decades, mostly through increased consumption of farmed fish, iron and calcium intake from fish have decreased, whilst no significant changes in intakes of zinc, vitamin A and vitamin B 12 have occurred, possibly reflecting lower overall nutritional quality of farmed fish [ 40 ]. Indeed, selenium levels in farmed salmon raised on increased levels of terrestrial-based diets have been shown to decrease by 50% [ 41 ]. In our study, we found no effect of salmon consumption on plasma concentrations of selenium, zinc or magnesium, which is perhaps expected considering the relatively low contribution of the salmon intervention to the RDA for these micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased total fish consumption in Bangladesh in the past two decades, mostly through increased consumption of farmed fish, iron and calcium intake from fish have decreased, whilst no significant changes in intakes of zinc, vitamin A and vitamin B 12 have occurred, possibly reflecting lower overall nutritional quality of farmed fish [ 40 ]. Indeed, selenium levels in farmed salmon raised on increased levels of terrestrial-based diets have been shown to decrease by 50% [ 41 ]. In our study, we found no effect of salmon consumption on plasma concentrations of selenium, zinc or magnesium, which is perhaps expected considering the relatively low contribution of the salmon intervention to the RDA for these micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fish, especially those which are marine-derived, are a good source of highly bioavailable dietary Se. However, Se levels can be up to 50 % lower in salmon fillets from fish fed vegetable oil and plant protein compared with fish oil and fish meal, corresponding to a reduction from 43 % to 21 % of the reference nutrient intake for Se for a 130 g portion ( 37 ) . Thus, although the reduced Se levels in the terrestrial-based diet satisfied the essential requirement for Se in the salmon, the shift in fish feed composition leads to a significant reduction in the supply of this essential micronutrient to the human diet.…”
Section: Effects Of Fish Production Regimes On Levels Of Long-chain Nmentioning
confidence: 99%
“…Because of a rapid growth in aquaculture and limited access to marine resources, fish oil and fish meal in feeds for carnivorous marine species such as Atlantic salmon (Salmo salar) have increasingly been replaced with plant ingredients over the past decades (43). Selenium (Se) is one of the essential minerals that there are higher levels of in fish meal than in plant feed ingredients (4). A decline of Se in Norwegian-produced commercial salmon feed during the last decade has been attributed to the decreased inclusion of fish meal (38).…”
mentioning
confidence: 99%
“…A decline of Se in Norwegian-produced commercial salmon feed during the last decade has been attributed to the decreased inclusion of fish meal (38). Se concentration in Atlantic salmon flesh was lower when fed on plant protein replacement feeds compared with marine protein feeds (4). Se is a well-known essential trace element (41) that is active as part of functional selenoproteins (24) involved in physiological processes such as antioxidant defense (glutathione peroxidases) (41) and thyroid homeostasis (deiodinases) (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation